2002
DOI: 10.1055/s-2002-33595
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies to Bovine Beta-Casein in Diabetes and Other Autoimmune Diseases

Abstract: Cow's milk is thought to be an environmental trigger for autoimmune response in Type 1 diabetes. In the present study, our aim was to investigate the antibody response to bovine beta-casein in different immune- and non-immune-mediated diseases and to establish whether such an antibody response is specific to Type 1 diabetes. We measured antibodies to bovine beta-casein using an enzyme-linked immunosorbent assay in a total of 519 sera from subjects as follows: 71 patients with Type 1 diabetes, 33 patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 19 publications
1
16
0
1
Order By: Relevance
“…Increased levels of antibodies reactive with dietary proteins such as cow’s milk proteins have been well studied in patients with CD and T1D [12,48,49,50]. Rodriguez-Juan et al [49] found that the level of antibodies to bovine serum albumin was significantly higher in CD patients and in those T1D patients who had antibodies to reticulin, endomysium or gliadin compared with controls.…”
Section: Discussionmentioning
confidence: 99%
“…Increased levels of antibodies reactive with dietary proteins such as cow’s milk proteins have been well studied in patients with CD and T1D [12,48,49,50]. Rodriguez-Juan et al [49] found that the level of antibodies to bovine serum albumin was significantly higher in CD patients and in those T1D patients who had antibodies to reticulin, endomysium or gliadin compared with controls.…”
Section: Discussionmentioning
confidence: 99%
“…Case-control studies have also found associations between cow's milk antibodies and T1D see e.g. (Sarugeri et al, 1999;Monetini et al, 2002), but some form of reverse causality cannot be excluded as alternative explanations for the association described in these studies. Although an early study indicated a role of so-called molecular mimicry between a protein in cow's milk and a -cell antigen (Karjalainen et al, 1992), it was subsequently refuted (Rønningen et al, 1998).…”
Section: Breast-feeding and Cow's Milkmentioning
confidence: 82%
“…IgG and IgM antibodies to cows' milk proteins can be higher in serum from persons with T1DM. IgG antibodies against casein have also been found to be increased in Type 1 diabetic patients, though not significantly so (Monetini et al, 2002).…”
Section: Introductionmentioning
confidence: 94%